Faktor-Faktor Yang Memengaruhi Pemilihan Alat Kontrasepsi KB Suntik 3 Bulan - Br Surbakti, Sempa Kita; Purnamasari, Eka; Agussamad, Indra; Sihombing, Verti; Sitompul, Lewi (MIDWIFERY JOURNAL, 2023)
In 2019, the world population reached 7.7 billion people. This number will increase by 1.08% from 2018, equivalent to 7.6 billion people. Over the past decade, the world's population has grown steadily at an annual rate of 1-1.2% per year. In 2050 the world population is estimated to only grow by 0.53%, the maternal mortality ratio is a measure of the level of service provided to mothers during childbirth.The aim of the research was to determine the factors that influence the 3-month injectable birth control contraceptive in Pekan Sawah Village. Carrying out research in the Pekan Sawah village.The research design used was descriptive with a cross sectional design. The research sample was all 92 women. The data collection instrument was a questionnaire regarding age, knowledge, education, parity and the choice of 3-month injectable birth control contraception. Data were analyzed using the Chi Square test.Univariate results: 92 respondents, the majority of respondents' ages were in the 21-35 years category, 35 people (38%), most had sufficient knowledge, 65 people (70.7%), most had secondary education, 49 people (53.5%), most had parity. 28 people (30.4%) were in category 2, most of the 3-month family planning injections were in the sufficient category, 76 people (82.6%). Bivariate results show that there is a relationship between the factors age (pvalue=0.008), knowledge (pvalue=0.036), education pvalue=(0.05), and parity (pvalue=0.014) in selecting a 3-month injectable birth control contraceptive.To increase Health Promotion and health motivation through IEC (Communication, Information and Education) regarding Family Planning and contraceptives does not only involve facilities at Health Institutions but also all families. Keywords: 3-month injectable contraceptive, knowledge, education ABSTRAK Pada tahun 2019, Populasi dunia mencapai 7,7 miliar jiwa. Jumlah ini akan meningkat 1,08% dari 2018 setara dengan 7,6 miliar orang. Selama dekade terakhir, populasi dunia telah tumbuh terus pada tingkat tahunan sebesar 1-1,2% per tahun. Pada tahun 2050 populasi dunia diperkirakan hanya tumbuh sebesar 0,53%, rasio kematian ibu merupakan ukuran tingkat pelayanan yang diberikan kepada ibu saat melahirkan.Tujuan penelitian untuk mengetahui faktor-faktor yang mempengaruhi alat kontrasepsi KB suntik 3 bulan doi Desa Pekan Sawah. Pelaksanaan penelitian di desa pekan sawah.Desain penelitian yang digunakan ialah deskriptif dengan rancangan cross sectional. Sampel penelitian adalah seluruh wanita yang berjumlah 92 orang. Instrumen pengumpulan data berupa kuesioner mengenai umur, pengetahuan, pendidikan, paritas dan pemilihan kontrasepsi KB Suntik 3 Bulan. Data dianalisis dengan uji Chi Square.Hasil Univariat 92 responden yang mayoritas umur responden berada pada kategori 21-35 tahun sebanyak 35 orang (38%), sebagian besar pengetahuan Cukup sebanyak 65 orang (70.7%), Sebagian besar pendidikan Menengah sebanyak 49 orang (53.5%), sebagian besar paritas berada pada kategori 2 sebanyak 28 orang (30.4%), sebagian besar suntik KB 3 Bulan berada pada kategori cukup sebanyak 76 orang (82.6%). Hasil Bivariat menunjukkan adanya hubungan faktor umur (pvalue=0,008), pengetahuan (pvalue=0,036), pendidikan pvalue=(0,05), dan paritas (pvalue=0,014) dalam pemilihan alat kontrasepsi KB suntik 3 Bulan.Untuk meningkatkan Promosi Kesehatan dan motivasi kesehatan melalui KIE (Komunikasi, Informasi, dan Edukasi) mengenai Keluarga Berencana dan alat-alat kontrasepsi tidak hanya melibatkan sarana di Lembaga Kesehatan tetapi juga seluruh para keluarga. Kata Kunci: KB suntik 3 bulan, pengetahuan, pendidikan